2021
DOI: 10.1126/sciadv.abg6707
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and opponent thermosensors use flexible cross-inhibition to orchestrate thermal homeostasis

Abstract: Body temperature homeostasis is essential and reliant upon the integration of outputs from multiple classes of cooling- and warming-responsive cells. The computations that integrate these outputs are not understood. Here, we discover a set of warming cells (WCs) and show that the outputs of these WCs combine with previously described cooling cells (CCs) in a cross-inhibition computation to drive thermal homeostasis in larval Drosophila. WCs and CCs detect temperature changes using overlapping combinations of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 71 publications
5
60
0
Order By: Relevance
“…We found that most 2nd-order neurons received direct input from a single SN type (Fig. 4B), with some exceptions, including olfactory local neurons that also received from gustatory and thermo warm SNs, as previously reported ( 45, 48 ). 3rd-order neurons were more often shared across modalities and, by the 4th-order, most neurons were shared across modalities (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We found that most 2nd-order neurons received direct input from a single SN type (Fig. 4B), with some exceptions, including olfactory local neurons that also received from gustatory and thermo warm SNs, as previously reported ( 45, 48 ). 3rd-order neurons were more often shared across modalities and, by the 4th-order, most neurons were shared across modalities (Fig.…”
Section: Resultssupporting
confidence: 86%
“…We classified input neurons based on their known sensory modalities. Olfactory ( 45 ), gustatory ( 47, 66, 101 ), thermosensory ( 48, 102 ), visual ( 46 ), gut ( 47, 103, 104 ) and respiratory state SNs ( 105 ) project directly to the brain. Somatosensory ANs from the nerve cord received direct or indirect input from mechanosensory ( 29, 38, 106 ), nociceptive ( 38, 107109 ) and proprioceptive SNs ( 110, 111 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cool and warm IR receptors are sufficient for cool preferences between 18 • C and 25 • C IR25a and IR93a are co-receptor IRs for both cool and warm receptors (Knecht et al, 2016;Ni et al, 2016;Hernandez-Nunez et al, 2021). To confirm the function of IR25a and IR93a in 18 • C preferences, we performed rescue experiments.…”
Section: Ir93a and Ir92a Are Not Expressed In The Same Neuronsmentioning
confidence: 99%
“…We focus specifically on studies of adult Drosophila . There are a number of articles describing behavioral flexibility in Drosophila larvae that are not discussed here (e.g., Schroll et al, 2006 ; Schleyer et al, 2011 , 2020 ; Allen et al, 2017 ; Mancini et al, 2019 ; Eschbach et al, 2020 ; Miroschnikow et al, 2020 ; Slankster et al, 2020 ; Gowda et al, 2021 ; Hernandez-Nunez et al, 2021 ; Vogt et al, 2021 ). Our goal is to highlight generalizable neural circuitry frameworks for how sensory cues, state, and experience are integrated to guide the flexible selection of appropriate behavior.…”
Section: Introductionmentioning
confidence: 99%